The ability of liposomes, tailored for blood–brain barrier targeting, to reach the brain is dramatically affected by the disease state. (March 2018) - Magro, Roberta Dal; Cox, Alysia; Zambelli, Vanessa; Mancini, Simona; Masserini, Massimo; Re, Francesca
Aim: To investigate if and how the ability of liposomes, previously designed for Alzheimer's therapy, to reach the brain changes in aging/pathological conditions with respect to the healthy state.Methods: Biodistribution and pharmacokinetics of liposomes in young or aged healthy mice and in an Alzheimer's mouse model were measured by radiochemical techniques. The expression of brain receptors and structural proteins was evaluated by Western blot.Results: At equal blood levels, the amount and integrity of liposomes in the brain were dramatically lower in Alzheimer's or aged mice, with respect to young animals. These differences are likely attributable to molecular alterations in the brain vasculature.Conclusion: Brain alterations in pathology or aging should be considered in the design of drug delivery systems for brain targeting.